Prodasineura hoffmanni sp. nov. (Odonata, Platycnemididae, Disparoneurinae) from eastern Cambodia - Kosterin, Oleg E. (Zootaxa, 2015)
Prodasineura hoffmanni sp. nov. is described from Annamense Mountains in eastern Cambodia (holotype: Cambodia, Mondulkiri Province, 4.2 km SE of Dak Dam village, 12°23'10-18'' N 107°19'22-30'' E, 877-878 m asl, 14. VI. 2014, RMNH). The species has a blue pattern, and the male is characterised by medium-broad blue stripes on synthorax and blue colour at the end of the abdomen confined to a tiny spot on S9, dorsum of S10 and cerci. A female of P. doisuthepensis Hoess, 2007 is described. Based on original descriptions, the following synonymy is proposed: Prodasineura fujianensis Xu, 2006 = Prodasineura huai Zhou et Zhou, 2007, syn. n.